The Role of Adab in the Process of Seeking and Practicing Knowledge from an Islamic Perspective: A Literature Review - Abdul Hamid (Formad English Foundation NTB Jakarta, 2025)
This study is motivated by the growing concern over the declining ethical conduct among students and the limited scholarly attention given to the role of adab in the process of seeking and practicing knowledge within contemporary Islamic education. While numerous studies address cognitive and pedagogical aspects, fewer explore the spiritual-ethical foundations that shape meaningful learning. Therefore, this literature review aims to examine how adab functions as a core element in the acquisition, internalization, and application of knowledge from an Islamic perspective. A qualitative literature review method was employed by analyzing classical Islamic works, contemporary academic publications, and key writings of prominent Muslim scholars. The analysis focused on conceptual frameworks of adab, its principles in learning, and its implications for educational practice. The review process included thematic analysis to identify recurring constructs and patterns related to ethical discipline, intellectual humility, teacher–student relationships, and the transformative purpose of knowledge. The findings indicate that adab is foundational in shaping learners’ intentions, attitudes, and behaviors, serving as a moral compass throughout the learning process. Classical scholars emphasize that knowledge devoid of adab leads to superficial understanding and weak character formation. Furthermore, adab fosters sincerity, respect for teachers, disciplined inquiry, and responsible application of knowledge in daily life. The review also highlights that integrating adab into modern education can strengthen spiritual awareness, promote holistic learning, and enhance students’ moral resilience. In conclusion, adab plays a central role in ensuring that the pursuit of knowledge aligns with Islamic ethical values and contributes to the development of morally grounded individuals.